2016
DOI: 10.1002/1873-3468.12242
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by GOSPEL protein of GAPDH aggregation induced by nitric oxide donor and its inhibition by NAD+

Abstract: Edited by Barry HalliwellGlyceraldehyde-3-phosphate dehydrogenase's (GAPDH's) competitor of Siah Protein Enhances Life (GOSPEL) is the protein that competes with Siah1 for binding to GAPDH under NO-induced stress conditions preventing Siah1-bound GAPDH nuclear translocation and subsequent apoptosis. Under these conditions, GAPDH may also form amyloid-like aggregates proposed to be involved in cell death. Here, we report the in vitro enhancement by GOSPEL of NO-induced GAPDH aggregation resulting in the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…This hypothesis was not developed further. Moreover, it was shown that GOSPEL stimulates the formation of amyloid aggregates induced by the S -nitrosylation of GAPDH [ 55 ]. Then, one more mechanism of signal transduction mediated by S -nitrosylated GAPDH was proposed, according to which the nitric oxide group is transferred from S -nitrosylated GAPDH to nuclear proteins, including the deacetylating enzyme sirtuin-1 (SIRT1), histone deacetylase-2 (HDAC2), and DNA-activated protein kinase (DNA-PK) [ 56 ].…”
Section: Development Of Ideas About the Induction Of Apoptosis With The Participation Of Gapdhmentioning
confidence: 99%
“…This hypothesis was not developed further. Moreover, it was shown that GOSPEL stimulates the formation of amyloid aggregates induced by the S -nitrosylation of GAPDH [ 55 ]. Then, one more mechanism of signal transduction mediated by S -nitrosylated GAPDH was proposed, according to which the nitric oxide group is transferred from S -nitrosylated GAPDH to nuclear proteins, including the deacetylating enzyme sirtuin-1 (SIRT1), histone deacetylase-2 (HDAC2), and DNA-activated protein kinase (DNA-PK) [ 56 ].…”
Section: Development Of Ideas About the Induction Of Apoptosis With The Participation Of Gapdhmentioning
confidence: 99%
“…hTPI activity was measured in the direction of DHAP conversion to G3P. The reaction was coupled to purified recombinant hGAPDH [35] under conditions in which the overall reaction was limited by the isomerase reaction. The increase in the absorbance at 340 nm, due to the formation of NADH (extinction coefficient = 6220 M −1 cm −1 ), was monitored at 30 °C using a Shimadzu UV-PC 1600 spectrophotometer equipped with a Peltier control of temperature.…”
Section: Htpi Activity Assaymentioning
confidence: 99%